Integration of Physical and Spiritual Dimensions in Youth Education: The Concept of Sufi Education by KH. M. Qoyim Ya'qub - Mihmidaty Ya'cub; Ahmad Shofiyul Himami; Mia Rahmawati; Ati Dingpanoh (LP3M IAI Al Urwatul Wutsqo Jombang, 2025)
This study aims to analyze the concept of Sufism-based Islamic education for adolescents from the perspective of KH. M. Qoyyim Ya’qub and its relevance to character development in the modern era. The study is motivated by the growing imbalance between physical (jasadiyah) and spiritual (ruhiyah) dimensions in contemporary Islamic education, which has contributed to various adolescent problems such as moral degradation, weak self-control, and spiritual crisis. This research employs a library research approach using a philosophical perspective and descriptive-analytical method. The data were collected from the works of KH. M. Qoyyim Ya’qub as primary sources, supported by scholarly literature on Islamic education, Sufism, character education, and adolescent developmental psychology. Data analysis was conducted through content analysis focusing on educational concepts, stages, methods, and value orientations of Sufism-based education. The findings reveal that KH. M. Qoyyim Ya’qub’s Sufism-based educational concept is structured systematically and gradually through four main stages: shari‘ah, tariqah, haqiqah, and ma‘rifah. This approach emphasizes the internalization of spiritual values, habituation of religious practices, the exemplary role of the spiritual guide (mursyid), and the integration of spiritual education with social life and practical skills. Sufism-based education is positioned not merely as a ritual practice but as a holistic pedagogical approach aimed at fostering moral awareness, emotional maturity, and spiritual resilience among adolescents. This study contributes theoretically to the development of an adaptive framework of Sufism-based Islamic education for modern adolescents and practically offers an alternative model of character education for Islamic educational institutions. However, this study is limited by the absence of empirical field data; therefore, future research employing qualitative field studies is recommended to further examine the effectiveness of this educational model.